Interaction with macrophages attenuates equine fibroblast‐like synoviocyte ADAMTS5 (aggrecanase‐2) gene expression following inflammatory stimulation. Issue 8 (24th April 2018) - Morgan, Rhiannon E.; Clegg, Peter D.; Hunt, John A.; Innes, John F.; Tew, Simon R.
ABSTRACT: The joint synovium consists of a heterogeneous cell population, chiefly comprised of macrophages, and fibroblast‐like synoviocytes (FLS). An inter‐species co‐culture model was developed to examine interactions between these cells. Equine FLS and the canine macrophage line DH82 were differentially labeled using fluorescent markers and results from direct co‐culture compared with those from both indirect co‐culture, and conditioned media experiments. The transcript expression of IL‐1β, IL‐6, ADAMTS4, and ADAMTS5 in each cell type were determined using species‐specific qPCR assays. Lipopolysaccharide stimulation of EFLS rapidly increased IL‐1β, IL‐6, ADAMTS4, and ADAMTS5 mRNAs. The induction of ADAMTS5 was significantly reduced when equine FLS were cultured with DH82 cells directly or indirectly. Exposure of equine FLS to denatured conditioned media also significantly reduced ADAMTS5 induction. DH82 cells increased interleukin‐1β expression substantially following LPS stimulation. However, knockdown of interleukin‐1β in DH82 cells, or inhibition of NF‐κB in equine FLS prior to co‐culture did not change the inhibitory effect on equine FLS ADAMTS5 gene expression. This work indicates that macrophages can influence FLS gene expression through a soluble mediator, and modulate the expression of an enzyme critical in osteoarthritis pathology during inflammatory stimulation. © 2018 The Authors. Journal of Orthopaedic Research ® Published by WileyPeriodicals, Inc. on behalf of the Orthopaedic Research Society. J Orthop Res 36:2178–2185, 2018.